2014
DOI: 10.1063/1.4900779
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of solid-gas reactions characterized by scanning AC nano-calorimetry with application to Zr oxidation

Abstract: Scanning AC nano-calorimetry is a recently developed experimental technique capable of measuring the heat capacity of thin-film samples of a material over a wide range of temperatures and heating rates. Here we describe how this technique can be used to study solid-gas phase reactions by measuring the change in heat capacity of a sample during reaction. We apply this approach to evaluate the oxidation kinetics of thin-film samples of zirconium in air. The results confirm parabolic oxidation kinetics with an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The samples were heated to approximately 1,300 K at average heating rates varying from 13 K/s to 21,000 K/s, and then cooled to room temperature at a rate of approximately 5,000 K/s. Previous work has demonstrated that under these experimental conditions sample oxidation effects are negligible [27].…”
Section: Sample Preparation and Nanocalorimetry Measurementsmentioning
confidence: 85%
“…The samples were heated to approximately 1,300 K at average heating rates varying from 13 K/s to 21,000 K/s, and then cooled to room temperature at a rate of approximately 5,000 K/s. Previous work has demonstrated that under these experimental conditions sample oxidation effects are negligible [27].…”
Section: Sample Preparation and Nanocalorimetry Measurementsmentioning
confidence: 85%
“…The technique can be applied to study a broad range of reactions, e.g. high temperature solid-gas reactions of thin-film materials, or the reaction kinetics under a wide range of scanning rates, just to name a few [24,25].…”
Section: Scanning Ac Nanocalorimetrymentioning
confidence: 99%
“…If we assign all droplets with volume v i (and thus a surface or interfacial area of s i ) in the distribution to group i, and if we denote the number of droplets and the nucleation frequency per droplet in that group by n i and , respectively, the rate of nucleation then follows the law of radioactive decay [70] 20) provided the number of droplets is sufficiently large. For bulk nucleation, the expected nucleation frequency is given by 25) where m is the total number of groups in the distribution and V is the total volume of i I droplets at a given time. Equations (4.24) and (4.25) are very general and hold for any temperature history, but they are not very useful in the analysis of experimental data because it is difficult to resolve the nucleation frequency for islands of different size.…”
Section: Application To Nucleation Theorymentioning
confidence: 99%